Pengembangan Kawasan Transmigrasi dalam Rangka Meningkatkan Pembangunan pada Dinas Transmigrasi dan Tenaga Kerja - Rinjani Vira Ningsih; Najamuddin Najamuddin (Journal of Social and Policy Issues, 2021)
The territory of the Unitary State of the Republic of Indonesia with a dense population, uneven and unbalanced distribution causes development and development to become less stable, resulting in inequality between regions. Transmigration was first carried out after Indonesia's independence in 1950, while in West Aceh Regency the first time it received transmigrants was in 1982/1983. Transmigration is a constitutional mandate (UU No. 15 of 1997) that needs to be implemented. The government or executive institutions have a big responsibility in carrying out the mandate of the Act with the principles of good governance. One of the principles of good governance is to conduct transparent and accountable planning. The role of transmigration is very important for regional development, it can be seen in various aspects of the development of production factors. The development and development of transmigration areas aims to improve the quality and quantity as well as to build regional self-reliance. This study used a qualitative method through a descriptive approach so that in collecting data the researchers used observation, interviews, and documentation techniques. The results of the study explain that the current development and development in each transmigration area has not fully met the quality, because there are many shortcomings that are needed by transmigrants. The process of changing the development of transmigration areas has now been carried out in a comprehensive manner, but not yet fully distributed, such as providing guidance and counselling to the community and providing the best facilities from the provinces and districts.